Seamless integration of MetaEdit+ and eclipse to combine modeling and coding - Wirpi, Olli (2012)
Tool integration tries to help users by automating processes in software development. In literature integration is mostly shown from technical point of view leaving user related issues outside. In this paper tool integration is looked also from the perspective of software engineering process and the user involved in the process. Another aspect will be integrating design models and code. A case of tool integration will be presented. The first tool is MetaEdit+ which is a Domain-Specific Modeling environment. The other tool is Eclipse which is used for traditional software engineering. The integration aims to combine the modeling and coding activities which together support metamodelers and modelers in their work.